Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the definite integral \(\int_4^9\left(\frac{3}{\sqrt{x}}-\frac{1}{x \sqrt{x}}\right) dx\), let's break it down step-by-step:
1. Rewrite the integrand:
The given integrand is \(\frac{3}{\sqrt{x}} - \frac{1}{x \sqrt{x}}\). Let's rewrite each term in a simpler form:
[tex]\[ \frac{3}{\sqrt{x}} = 3x^{-\frac{1}{2}} \][/tex]
[tex]\[ \frac{1}{x \sqrt{x}} = \frac{1}{x \cdot x^{\frac{1}{2}}} = \frac{1}{x^{\frac{3}{2}}} = x^{-\frac{3}{2}} \][/tex]
Therefore, the integrand becomes:
[tex]\[ 3x^{-\frac{1}{2}} - x^{-\frac{3}{2}} \][/tex]
2. Integrate each term separately:
We now need to find the antiderivative of each term:
[tex]\[ \int 3x^{-\frac{1}{2}} \, dx \quad \text{and} \quad \int x^{-\frac{3}{2}} \, dx \][/tex]
For the first term:
[tex]\[ \int 3x^{-\frac{1}{2}} \, dx = 3 \int x^{-\frac{1}{2}} \, dx = 3 \cdot \frac{x^{\frac{1}{2}}}{\frac{1}{2}} = 3 \cdot 2x^{\frac{1}{2}} = 6x^{\frac{1}{2}} \][/tex]
For the second term:
[tex]\[ \int x^{-\frac{3}{2}} \, dx = \int x^{-\frac{3}{2}} \, dx = \frac{x^{-\frac{3}{2}+1}}{-\frac{3}{2}+1} = \frac{x^{-\frac{1}{2}}}{-\frac{1}{2}} = -2x^{-\frac{1}{2}} \][/tex]
3. Combine the antiderivatives:
Combining these results, the antiderivative of the integrand is:
[tex]\[ 6x^{\frac{1}{2}} - 2x^{-\frac{1}{2}} \][/tex]
4. Evaluate the definite integral:
We now need to evaluate the antiderivative at the upper and lower limits (9 and 4):
[tex]\[ \left[ 6x^{\frac{1}{2}} - 2x^{-\frac{1}{2}} \right]_4^9 \][/tex]
Calculate at \(x = 9\):
[tex]\[ 6 \cdot 9^{\frac{1}{2}} - 2 \cdot 9^{-\frac{1}{2}} = 6 \cdot 3 - 2 \cdot \frac{1}{3} = 18 - \frac{2}{3} = 18 - 0.66666666666667 = 17.33333333333333 \][/tex]
Calculate at \(x = 4\):
[tex]\[ 6 \cdot 4^{\frac{1}{2}} - 2 \cdot 4^{-\frac{1}{2}} = 6 \cdot 2 - 2 \cdot \frac{1}{2} = 12 - 1 = 11 \][/tex]
Taking the difference:
[tex]\[ 17.33333333333333 - 11 = 6.33333333333333 \][/tex]
Therefore, the value of the definite integral \(\int_4^9\left(\frac{3}{\sqrt{x}}-\frac{1}{x \sqrt{x}}\right) dx\) is:
[tex]\[ 5.66666666666667 \][/tex]
1. Rewrite the integrand:
The given integrand is \(\frac{3}{\sqrt{x}} - \frac{1}{x \sqrt{x}}\). Let's rewrite each term in a simpler form:
[tex]\[ \frac{3}{\sqrt{x}} = 3x^{-\frac{1}{2}} \][/tex]
[tex]\[ \frac{1}{x \sqrt{x}} = \frac{1}{x \cdot x^{\frac{1}{2}}} = \frac{1}{x^{\frac{3}{2}}} = x^{-\frac{3}{2}} \][/tex]
Therefore, the integrand becomes:
[tex]\[ 3x^{-\frac{1}{2}} - x^{-\frac{3}{2}} \][/tex]
2. Integrate each term separately:
We now need to find the antiderivative of each term:
[tex]\[ \int 3x^{-\frac{1}{2}} \, dx \quad \text{and} \quad \int x^{-\frac{3}{2}} \, dx \][/tex]
For the first term:
[tex]\[ \int 3x^{-\frac{1}{2}} \, dx = 3 \int x^{-\frac{1}{2}} \, dx = 3 \cdot \frac{x^{\frac{1}{2}}}{\frac{1}{2}} = 3 \cdot 2x^{\frac{1}{2}} = 6x^{\frac{1}{2}} \][/tex]
For the second term:
[tex]\[ \int x^{-\frac{3}{2}} \, dx = \int x^{-\frac{3}{2}} \, dx = \frac{x^{-\frac{3}{2}+1}}{-\frac{3}{2}+1} = \frac{x^{-\frac{1}{2}}}{-\frac{1}{2}} = -2x^{-\frac{1}{2}} \][/tex]
3. Combine the antiderivatives:
Combining these results, the antiderivative of the integrand is:
[tex]\[ 6x^{\frac{1}{2}} - 2x^{-\frac{1}{2}} \][/tex]
4. Evaluate the definite integral:
We now need to evaluate the antiderivative at the upper and lower limits (9 and 4):
[tex]\[ \left[ 6x^{\frac{1}{2}} - 2x^{-\frac{1}{2}} \right]_4^9 \][/tex]
Calculate at \(x = 9\):
[tex]\[ 6 \cdot 9^{\frac{1}{2}} - 2 \cdot 9^{-\frac{1}{2}} = 6 \cdot 3 - 2 \cdot \frac{1}{3} = 18 - \frac{2}{3} = 18 - 0.66666666666667 = 17.33333333333333 \][/tex]
Calculate at \(x = 4\):
[tex]\[ 6 \cdot 4^{\frac{1}{2}} - 2 \cdot 4^{-\frac{1}{2}} = 6 \cdot 2 - 2 \cdot \frac{1}{2} = 12 - 1 = 11 \][/tex]
Taking the difference:
[tex]\[ 17.33333333333333 - 11 = 6.33333333333333 \][/tex]
Therefore, the value of the definite integral \(\int_4^9\left(\frac{3}{\sqrt{x}}-\frac{1}{x \sqrt{x}}\right) dx\) is:
[tex]\[ 5.66666666666667 \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.